The landscape of cultural-historical psychology in BRICS+ countries: a bibliometric analysis - Shvedovskaya, A.A.; Ponomareva, V.V.; Korneev, A.A.; Samorodov, N.V. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
Context and relevance. The active development of cultural-historical psychology within the framework of international research demonstrates a significant expansion in the geographical distribution of publications over the past two decades, notably driven by the increasing contributions of BRICS+ countries. Nevertheless, the dynamics of publication activity, the structure of international collaboration, and the thematic evolution of cultural-historical psychology remain underexplored from a bibliometric perspective. Objective. This study aims to conduct a bibliometric analysis of the publication landscape in cultural-historical psychology between 2005 and 2024, with particular attention to the contribution of BRICS+ countries. Research Questions. The study examined: 1) the dynamics and geographical distribution of publication activity in the field of cultural-historical psychology, including the contribution of BRICS+ countries, over the period 2005-2024; 2) the structure of international scientific collaboration and the distribution of scientific influence; 3) the thematic structure of the field and its transformation over the past two decades; and 4) the contribution of the journal Cultural-Historical Psychology to the development and internationalisation of scientific communication. Methods and materials. The study incorporates: 1) a corpus of 4,332 publications identified through key terms relevant to the cultural-historical approach; 2) 947 publications from the journal Cultural-Historical Psychology; and 3) 949 publications citing articles from the same journal, sourced from Scopus, OpenAlex, and eLibrary.ru. The bibliometric analysis employed PRISMA protocols, R (bibliometrix), VOSviewer, and Python-based analytical tools. Results. The findings reveal a steady and, in some cases, accelerating growth in publication activity across BRICS+ countries: sevenfold in Russia, 3,7 times in Brazil, and 4,8 times in China over the study period. Publications from BRICS+ countries display a thematic shift towards educational and developmental issues. Despite increasing international citations, scientific collaboration within the BRICS+ bloc remains limited. The journal Cultural-Historical Psychology, which will mark its twentieth anniversary in 2025, occupies a central position in the publication landscape: it brings together authors from 49 countries, is cited in works from 61 countries, and more than one-third of citing publications appear in top-tier journals (Q1, International Scientific Journal & Country Ranking 2024). Conclusions. The publication landscape of cultural-historical psychology is characterised by global growth, with BRICS+ countries assuming an increasingly prominent role. Strengthening international cooperation within the BRICS+ bloc and fostering sustainable transnational networks represent key prospects for further advancement. The journal Cultural-Historical Psychology continues to serve as a major international scientific platform and contributes to the consolidation of the publication core within the field. Контекст и актуальность. Активное развитие культурно-исторической психологии в структуре международных исследований демонстрирует, что за последние два десятилетия география публикаций в этой области существенно расширилась, в том числе за счет нарастающего вклада стран БРИКС+. При этом динамика публикационной активности, структура международного сотрудничества и тематическая эволюция культурно-исторической психологии остаются малоизученными в контексте библиометрической оценки. Цель: провести библиометрический анализ публикационного ландшафта культурно-исторической психологии в период 2005-2024 годов, определив вклад стран БРИКС+ в его развитие. Исследовательские вопросы. В исследовании проанализированы: 1) динамика и география публикационной активности в области культурно-исторической психологии, включая вклад стран БРИКС+, за период 2005-2024 годов; 2) структура международной научной кооперации и распределение научного влияния; 3) тематическая структура и ее трансформация за два десятилетия; 4) вклад журнала «Культурно-историческая психология» в развитие и интернационализацию научной коммуникации. Методы и материалы. В исследование включены: 1) 4332 публикации, отобранные по релевантным культурно-историческому подходу ключевым словам; 2) 947 публикаций в журнале «Культурно-историческая психология»; 3) 949 публикаций, цитирующих публикации из журнала «Культурно-историческая психология», из баз: Scopus, OpenAlex, eLibrary.ru. Библиометрический анализ выполнен с применением инструментов PRISMA, R (bibliometrix), VOSviewer, Python. Результаты. Установлено, что страны БРИКС+ демонстрируют поступательный и, в ряде случаев, ускоряющийся рост публикационной активности: в России - в 7 раз, в Бразилии - в 3,7 раза, в Китае - в 4,8 раза - за исследуемый период. В публикациях стран БРИКС+ зафиксировано тематическое смещение в сторону образовательной и возрастной проблематики. Международная кооперация внутри блока БРИКС+ остается ограниченной, несмотря на рост международной цитируемости. Журнал «Культурно-историческая психология», отмечающий в 2025 году свое 20-летие, занимает центральное место в публикационном ландшафте: он объединяет авторов из 49 стран, цитируется в публикациях из 61 страны, более трети процитировавших публикаций размещены в высокорейтинговых журналах (Q1, International Scientific Journal & Country Ranking 2024). Выводы. Публикационный ландшафт культурно-исторической психологии характеризуется глобальным ростом, в котором страны БРИКС+ играют все более значимую роль. Усиление международной кооперации внутри блока БРИКС+ и развитие устойчивых транснациональных сетей - важная перспектива для дальнейшего роста. Журнал «Культурно-историческая психология» продолжает выполнять ключевую функцию международной научной платформы и вносит вклад в формирование публикационного ядра культурно-исторической психологии.